The knowledge outcome of sixth grade students in private schools in Arabic grammar (Journal of the College of Basic Education, 2022)
It becomes clear to the researcher through her work that the reality of our students in our schools indicates through observation and follow-up that the weakness in the collection of grammatical rules is a noticeable matter from specialists, learners and students, so that it cannot be ignored (Sabri, 2003: p. 11) and despite the obsolescence of the efforts concerned with teaching Arabic, learners are still weak In the Arabic language, complaints are increasing about their low level of language, especially in the grammar of the Arabic language, and their ignorance of its priorities